Left femoral venous access for leadless pacemaker implantation: patient characteristics and outcomes. (24th May 2021) - Jelisejevas, J; Breitenstein, A; Hofer, D; Winnik, S; Steffel, J; Saguner, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Leadless pacing has become an alternative approach for patients requiring a single-chamber pacemaker. Conventionally, Leadless Micra Transcatheter Pacing System (TPS) pacemakers are implanted via a right femoral venous access. However, due to various reasons, a left sided femoral venous approach may benecessary. We hypothesized that a left sided femoral venous approach is as safe and effective as compared to a right sided approach. Objective: We assessed indications, procedural characteristics, safety and mid-term outcomes of Micra TPS implantation via a left femoral venous approach as compared to the conventional right sided approach. Methods and Results: In this retrospective single-center analysis, 143 consecutive patients undergoing Micra TPS implantation were included. 87% (125/143) underwent Micra TPS implantation via a right, and 13% (18/143) via a left femoral venous access. The mean age at implantation was 79.8 ± 7.5 years. Acute procedural success, mean procedure and fluoroscopy times as well as device parameters at implantation and follow-up (mean 15 ± 11.5 months) were similar between the two groups. Five major complications (3.5%) were encountered, all using a right-sided approach. After a transfemoral TAVI procedure, left femoral venous access was used in 42% of cases as compared to 8% in the remaining population (p = 0.003). Final leadless pacemaker position within the right ventricle was mid-septal in 82% (102/125) for right femoral access vs 72% (13/18) for left femoral access (p = 0.16).  In the remaining cases (28 %, 5/18), the device was placed infero-septal following a left femoral venous access, as compared to 14% (18/125) for a right sided approach (p = 0.19). No repositioning was needed in 68% (85/125) using a right femoral access vs 72% (13/ 18) patients with a left femoral access (p = 0.84). Conclusions: A left femoral venous access for Micra TPS implantation is safe and effective with an excellent implantation success rate similar to a conventional right femoral venous access without longer implantation and fluoroscopy times. The most frequent reason for choosing left- vs. right femoral venous access was a previous transfemoral TAVI procedure.